Język tekstów mistycznych w języku religijnym. Propozycja klasyfikacji = The language of mystical texts as a part of the religious language. Proposal for a classification - Rutkowska, Izabela (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article aims to show the place of mystical texts in classifying religious language. First, we had to define such terms as "the language of the mystic and mystical text`s language". Then we had to expose the classifications known in theolinguistics. A confrontation of these issues with the philology knowledge pictured the significant differences. The work, the mystical masterpiece in the philology eye, does not have the same theological value. In catholic theology, the main criterion of appraisement of the mystical text is the relationship between the author and God - not the lexical level.
Keywords: teolingwistyka; język religijny; teksty mistyczne; kościół katolicki; chrześcijaństwo; theoliguistics; religious language; mystical texts; Catholic Church; Christianity